2008
DOI: 10.1007/s00253-008-1697-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of co-substrates and inhibitors on the anaerobic O-demethylation of methyl tert-butyl ether (MTBE)

Abstract: Methyl tert-butyl ether (MTBE) contamination is widespread in aquifers near urban areas around the world. Since this synthetic fuel oxygenate is resistant to most physical methods of treating fuel-contaminated water, biodegradation may be a useful means of remediation. Currently, information on anaerobic MTBE degradation is scarce. Depletion has been observed in soil and sediment microcosms from a variety of locations and under several redox conditions, but the responsible organisms are unknown. We are studyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 50 publications
1
37
0
Order By: Relevance
“…Previous characterization of these enrichment cultures provided strong evidence that the initial attack on MTBE was mediated by bacteria (Youngster et al , 2008). Furthermore, although carbon flow was ultimately coupled to sulfidogenesis or methanogenesis, inhibition of the terminal electron‐accepting processes did not inhibit the initial transformation of MTBE (Somsamak et al , 2005, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Previous characterization of these enrichment cultures provided strong evidence that the initial attack on MTBE was mediated by bacteria (Youngster et al , 2008). Furthermore, although carbon flow was ultimately coupled to sulfidogenesis or methanogenesis, inhibition of the terminal electron‐accepting processes did not inhibit the initial transformation of MTBE (Somsamak et al , 2005, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The negative effect of toluene was also reported by Morales et al [2], who found that biodegradation of MTBE at 74 mg L 21 could not be achieved in the presence of toluene at a concentration of 87 mg L 21 . In contrast, some researchers reported that there were no effects of toluene or BTEX on MTBE degradation [3][4][5][6]. In these studies, the concentrations of toluene or BTEX were in the range of 0.5-176 mg L 21 , and these concentrations were two or three times less than those of MTBE.…”
Section: Introductionmentioning
confidence: 81%
“…In some recent studies, little or no biodegradation has been observed over long periods [3,4]. In other cases, rapid anaerobic biodegradation has been observed [5].…”
Section: Anaerobic Biodegradation Of Ethers Oxygenatesmentioning
confidence: 98%
“…Recent studies with these cultures have focused on the frequently noted similarities between anaerobic ether oxygenate biodegradation and corrinoid-dependent demethylations of methyl ethers catalyzed by acetogenic bacteria. Several methoxylated aromatic cosubstrates such as syringate stimulate anaerobic MTBE biodegradation and degradation of MTBE by ether-stimulated cultures is inhibited in a light-reversible process by propyl iodide, a distinctive feature of corrinoid-dependent reactions [5]. The microbial communities in several MTBE-degrading enrichment cultures have been investigated and shown to be dominated by microorganisms from several phylotypes including the Firmicutes phylum that contains acetogens known to O-demethylate aromatic ethers [10 ].…”
Section: Anaerobic Biodegradation Of Ethers Oxygenatesmentioning
confidence: 99%